Radiological features do not predict failure of two-stage arthroplasty for prosthetic joint infection: a retrospective case-control study. - Dunachie, S; Teh, J; Ejindu, V; Bejon, P; Pandit, H; Byren, I (BioMed Central, 2014)
BACKGROUND: The management of prosthetic joint infection is complex and there is a lack of standardisation of approaches. We evaluated the role of plain film radiography in predicting prosthesis failure after the first stage of a two-stage revision procedure in a retrospective case-control study. METHODS: Plain films for 41 patients aged 46 to 87 years (mean 69) were assessed by two musculoskeletal specialist radiologists for seven features (retained or new metalwork, retained cement or restrictor, new fracture, local antimicrobial delivery system and drain) we hypothesised may predict for failure. Inter-observer agreement was assessed by Kappa score and logistic regression analysis was performed to evaluate the relationship of the seven radiological features adjusting for patient age, gender and number of previous revisions. RESULTS: There was substantial inter-observer agreement, with a Kappa score of 0.73 (95% CI 0.72-0.74) for all data points collected. Concordance was 100% for evaluating the presence or absence of an antimicrobial delivery system or drain, with lower consensus for evaluating cement (Kappa 0.60, 95% CI 0.35-0.84) and fractures (Kappa 0.59, 95% CI 0.31-0.87). None of the variables' conditions significantly predicted failure. CONCLUSIONS: Our findings support the opinion that surgical expertise which maximizes removal of foreign material is sufficient in conjunction with antibiotic therapy.